Bandwidth Broadening of Piezoelectric Energy Harvesters Using Arrays of a Proposed Piezoelectric Cantilever Structure - Marwa S. Salem; Shimaa Ahmed; Ahmed Shaker; Mohammad T. Alshammari; Kawther A. Al-Dhlan; Adwan Alanazi; Ahmed Saeed; Mohamed Abouelatta (Micromachines, 2021)
One of the most important challenges in the design of the piezoelectric energy harvester is its narrow bandwidth. Most of the input vibration sources are exposed to frequency variation during their operation. The piezoelectric energy harvester’s narrow bandwidth makes it difficult for the harvester to track the variations of the input vibration source frequency. Thus, the harvester’s output power and overall performance is expected to decline from the designed value. This current study aims to solve the problem of the piezoelectric energy harvester’s narrow bandwidth. The main objective is to achieve bandwidth broadening which is carried out by segmenting the piezoelectric material of the energy harvester into n segments; where n could be more than one. Three arrays with two, four, and six beams are shaped with two piezoelectric segments. The effect of changing the length of the piezoelectric material segment on the resonant frequency, output power, and bandwidth, as well as the frequency response is investigated. The proposed piezoelectric energy harvesters were implemented utilizing a finite element method (FEM) simulation in a MATLAB environment. The results show that increasing the number of array beams increases the output power and bandwidth. For the three-beam arrays, at n equals 2, 6 mW output power and a 9 Hz bandwidth were obtained. Moreover, the bandwidth of such arrays covered around 5% deviation from its resonant frequency. All structures were designed to operate as a steel wheel safety sensor which could be used in train tracks.